Swedish technology teachers' attitudes to their subject and its teaching. Issue 2 (3rd April 2017) - Nordlöf, Charlotta; Höst, Gunnar E.; Hallström, Jonas
Abstract: Background: From previous research among science teachers it is known that teachers' attitudes to their subjects affect important aspects of their teaching, including their confidence and the amount of time they spend teaching the subject. In contrast, less is known about technology teachers' attitudes. Purpose: Therefore, the aim of this study is to investigate Swedish technology teachers' attitudes toward their subject, and how these attitudes may be related to background variables. Sample: Technology teachers in Swedish compulsory schools ( n = 1153) responded to a questionnaire about teachers' attitudes, experiences, and background. Methods: Exploratory factor analysis was used to inwvestigate attitude dimensions of the questionnaire. Groupings of teachers based on attitudes were identified through cluster analysis, and multinomial logistic regression was performed to investigate the role of teachers' background variables as predictors for cluster belonging. Results: Four attitudinal dimensions were identified in the questionnaire, corresponding to distinct components of attitudes. Three teacher clusters were identified among the respondents characterized by positive, negative, and mixed attitudes toward the subject of technology and its teaching, respectively. The most influential predictors of cluster membership were to be qualified for teaching technology, having participated in in-service-training, teaching at a school with a proper overall teaching plan for the subject of technology and teaching at a school with a defined number of teaching hours for the subject. Conclusions: The results suggest that efforts to increase technology teachers' qualifications and establishing a fixed number of teaching hours and an overall teaching plan for the subject of technology may yield more positive attitudes among teachers toward technology teaching. In turn, this could improve the status of the subject as well as students' learning.